2015
DOI: 10.1002/elsc.201400099
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐supplemented mixed bacterial cultures to produce hydrogen from paperboard mill wastewater

Abstract: Paperboard mill wastewater (PMW) mainly comprises complex compounds such as polysaccharides and lignin that are recalcitrant to microbial and enzymatic action. Surfactants supplementation was found to improve the enzymatic hydrolysis and reduce lignin content during anaerobic digestion process. However, much less attention has been given for the effectiveness of surfactants addition on hydrogen production from PMW under hyperthermophilic conditions. In this study, the mixed bacterial culture was supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition to that there are no significant effects found in the utilization and formation of organic acids in hydrogen production supplemented with surfactants. Paperboard mill wastewater was utilized as the source for hydrogen production with the utilization of surfactants like PEG 6000 and Tween 80 103,112 …”
Section: Surfactantsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to that there are no significant effects found in the utilization and formation of organic acids in hydrogen production supplemented with surfactants. Paperboard mill wastewater was utilized as the source for hydrogen production with the utilization of surfactants like PEG 6000 and Tween 80 103,112 …”
Section: Surfactantsmentioning
confidence: 99%
“…Trichoderma asperellum laccase was immobilized on Fe 3 O 4 @SiO 2 ‐Chitosan nanoparticles for delignification of lignocellulosic biomass and was utilized for the biohydrogen production with sweet sorghum stove as substrate. The immobilized laccase was found to have high lignin degradation potential than the free enzyme, which could be efficiently reused up to eight cycles 112 . Boshagh et al 113 immobilized E aerogens on multi‐walled carbon nanotube having carboxyl acid groups (MWCNT‐COOH) for the efficient hydrogen production and revealed that the immobilized E aerogens on MWCNT‐COOH resulted in higher biohydrogen yield (2.2 mol/mol glucose) when compared with free E aerogens .…”
Section: Applications Of Biocatalyst In Biohydrogen Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Egypt produces approximately 500 million cubic meters per year of industrial wastewater of which 50% is partially treated and the major portion is dumped into the sewerage network without treatment causing serious environmental problems . The cake processing industry generates a heavily polluted wastewater which is very rich in coarse suspended solids, lipids, COD, BOD 5 and nitrogen components .…”
Section: Introductionmentioning
confidence: 99%